2014
DOI: 10.5603/cj.a2013.0062
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of carvedilol and nebivolol on diastolic functions of the left ventricle in patients with non-ischemic heart failure

Abstract: Background: We investigated whether carvediolol or nebiovolol with vasodilator properties will produce different effects on diastolic function of the left ventricle (LV) in heart failure (HF) with low ejection fraction (EF).Methods: Sixty-one non-ischemic HF patients with EF £ 40% randomly received carvedilol (n = 31, 16 male) or nebivolol (n = 30, 19 DT prolonged (from 184 ± 40 to 218 ± 42 ms vs. from 193 ± 37 to 222 ± 36 ms, p = 0.71). Also, E/Ea ratio significantly decreased in each group (p = 0.01), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Consistently, Nebivolol has been reported to mitigate the expressions/activities of MMP-2 and MMP-9 (Ceron et al 2013). In this study, Nevibolol was used at the concentrations of 1, 5, and 10 μM, which are consistent with previous studies showing that Nebivolol exerts various pharmacological actions in a range of micromolar concentrations and are comparable to the concentrations used for treatment of patients (Dogan et al 2014). Consistently, it was shown that increasing amounts of the Nevibolol (from 1 to 25 μM) increased the production of nitric oxide and reduced the generation of ROS in endothelial cells (Cominacini et al 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Consistently, Nebivolol has been reported to mitigate the expressions/activities of MMP-2 and MMP-9 (Ceron et al 2013). In this study, Nevibolol was used at the concentrations of 1, 5, and 10 μM, which are consistent with previous studies showing that Nebivolol exerts various pharmacological actions in a range of micromolar concentrations and are comparable to the concentrations used for treatment of patients (Dogan et al 2014). Consistently, it was shown that increasing amounts of the Nevibolol (from 1 to 25 μM) increased the production of nitric oxide and reduced the generation of ROS in endothelial cells (Cominacini et al 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Some findings of this study on the effects of both agents on diastolic LV function were previously published elsewhere (17). Thus, the patient characteristics and laboratory and echocardiography findings were similar to those of the previously published study.…”
Section: Methodsmentioning
confidence: 57%
“…Thereafter, carvedilol or nebivolol was randomly started, and they were up-titrated as previously reported elsewhere (17). After the target or maximum tolerable dose, patients were evaluated in the outpatient clinic at the first, third, and sixth months.…”
Section: Methodsmentioning
confidence: 99%
“…At present, little data are available on the comparative effectiveness of carvedilol and nebivolol for HF. A recent study found that carvedilol and nebivolol appear to similarly improve LV diastolic functions in nonischemic HF patients [25]. However, that study did not involve an HF population with preserved EF.…”
Section: Discussionmentioning
confidence: 99%